2018
DOI: 10.3389/fphy.2018.00006
|View full text |Cite
|
Sign up to set email alerts
|

A Search for Two Types of Transverse Excitations in Liquid Polyvalent Metals at Ambient Pressure: An Ab Initio Molecular Dynamics Study of Collective Excitations in Liquid Al, Tl, and Ni

Abstract: Recent findings of pressure-induced emergence of unusual high-frequency contribution to transverse current spectral functions in several simple liquid metals at high pressures raised a question whether similar features can be observed in liquid metals at ambient conditions. We report here analysis of ab initio molecular dynamics-derived longitudinal and transverse current spectral functions and corresponding dispersions of collective excitations in liquid polyvalent metals Al, Tl, Ni. We have not found evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 30 publications
(34 reference statements)
6
14
0
Order By: Relevance
“…The exploiting of the GBA in this framework can be relevant because features in the dynamic structure factor possibly related to the mixing of polarizations have been observed experimentally [50,54,109,110] and by MD simulations [55,56,58] in several liquids. Similar developments could also support the understanding of the origin of the two-peak structure observed in the transverse current spectra of liquids in the high-frequency region, as attested by recent MD studies [57,111,112].…”
Section: Discussionsupporting
confidence: 67%
“…The exploiting of the GBA in this framework can be relevant because features in the dynamic structure factor possibly related to the mixing of polarizations have been observed experimentally [50,54,109,110] and by MD simulations [55,56,58] in several liquids. Similar developments could also support the understanding of the origin of the two-peak structure observed in the transverse current spectra of liquids in the high-frequency region, as attested by recent MD studies [57,111,112].…”
Section: Discussionsupporting
confidence: 67%
“…Later on in ab initio molecular dynamics (AIMD) simulations of liquid Li [19] revealed that at high pressures the transverse current spectral functions showed a two-peak structure, which became more pronounced with increasing pressure. Later on similar findings were observed even at ambient pressure in liquid Tl [20].…”
Section: Introductionsupporting
confidence: 73%
“…The appearance of another, high frequency branch in the transvese dispersion relation, had been reported first in some liquid metals at high pressure, i.e., Li, Na, Fe, Al and Pb, [2,[64][65][66]. Subsequently, it was also found in l-Tl and l-Pb [64,66,67] at ambient pressure.…”
Section: Collective Dynamicsmentioning
confidence: 87%